Prolactinoma in childhood and adolescence—Tumour size at presentation predicts management strategy: Single centre series and a systematic review and meta‐analysis. (26th December 2020) - Arya, Ved Bhushan; Aylwin, Simon J. B.; Hulse, Tony; Ajzensztejn, Michal; Kalitsi, Jennifer; Kalogirou, Nicolas; Bodi, Istvan; Thomas, Nick; Hampton, Tim; Kapoor, Ritika R.; Buchanan, Charles R.
Abstract: Objective: To report the clinical presentation, management and outcomes of young patients with prolactinomas (<20 years) and conduct a systematic review and meta‐analysis. Patients and Design: Clinical, biochemical and radiological data (1996‐2018) were collected from our centre. A systematic review and meta‐analysis of published literature (1994‐2019) on prolactinoma (age <20 years) were conducted. Both random and fixed effects meta‐analysis were used to pool outcomes across studies. Results 1 Case series: Twenty‐two patients (14 females) were identified; median age at diagnosis 15.7 years (range 13‐19); 12 patients (6 females) had a macroprolactinoma. Seven patients (macroprolactinoma‐6) had associated pituitary hormone deficiencies at presentation. Five patients (4 males) underwent surgical resection due to poor response to cabergoline or apoplexy. Patients undergoing surgery had larger tumours ( p  < .02) and higher serum prolactin concentration ( p  < .005). All patients with macroprolactinoma >20 mm required surgical intervention. Results 2 Systematic review and meta‐analysis: We selected 11 studies according to strict inclusion criteria describing 275 patients. Macroprolactinoma was more common in girls (78.7% [95% CI 70.5‐85.9]) than boys and was more frequent than microprolactinoma (56.6% [95% CI 48.4‐64.5]). In males, only 6/57 (10.5%) of tumours were microprolactinoma as compared to 102/198 (51.5%) microprolactinoma in females (risk difference −0.460; [95% CI −0.563 to −0.357]; p  < .001). Surgery was first‐line therapy in 18.9% patients, with another 15.4% requiring it as a second line (overall 31.3%). Conclusions: Macroprolactinoma, particularly if >20 mm, usually requires multimodal therapy including surgical intervention. While overall prolactinomas in <20 years age group are more common in females, the proportion of macroprolactinoma vs microprolactinoma is greater in males, particularly for large invasive tumours. Microprolactinoma is a rare diagnosis in adolescent males.